Feasibility study of Massive Open Online Course (MOOC) in supporting self determined learning in state islamic higher education - sumarsono sumarsono; Sutrisno Sutrisno; Agung Fatwanto (Institut Teknologi Dirgantara Adisutjipto, 2021)
The learning model in the digital era has changed from traditional face-to-face learning to online learning. This causes stuttering and uncertainty for educational institutions, including the State Islamic Religious University (PTKIN), especially the readiness of lecturers. Each lecturer has different models, strategies and learning media in managing the class according to their understanding and ability in online learning. This study aims to see the readiness of PTKIN lecturers for online learning through MOOCs media with a heutagogy approach using the e-learning system at their respective universities.The quantitative research method uses 5 elements of heutagogy and 1 element of MOOCs with 52 sampling data on PTKIN lecturers.The results show that lecturers have competence and readiness in using online learning technology, but there are weaknesses in lecturers' understanding in using the heutagogy approach in learning.